Laparoscopic en bloc resection of a para-cervical cancer with OHVIRA syndrome - Soshi Kusunoki; Kuan-Gen Huang; Angelito Magno (Elsevier, 2018)
Objective: There are some reports of cervical cancer with uterus didelphys but a case of clear cell carcinoma (CCCC) with Obstructed Hemivagina and Ipsilateral Renal Anomaly (OHVIRA) syndrome is extremely rare. The aim of this paper was to report a case of CCCC with OHVIRA syndrome and the difficulty in making a preoperative diagnosis. Case report: A 65 years old woman presented with postmenopausal bleeding and pelvic examination showed right paracervical mass. Preoperative confirmation of cervical carcinoma was difficult due to the location of the mass, which was inaccessible by cervical punch biopsy. Pelvic examination revealed a large mass in pelvic cavity without parametrial invasion and ultrasound showed approximately 70 mm cervical tumor. Laparoscopic surgery revealed clear cell carcinoma of the para-endocervix with OHVIRA syndrome. Conclusion: In the case of cervical carcinoma with OHVIRA syndrome, laparoscopic surgery is preferable for the diagnosis and management.